Reconstructing the History of Spanish Lexicography: The Nuevo diccionario de las plantas medicinales estudiadas bajo el punto de vista botánico, médico y farmacéutico (1876) - Camacho Niño, Jesús (Círculo de Lingüística Aplicada a la Comunicación, 2026)
The history of Spanish lexicography remains, in many respects, unexplored terrain. Despite the abundance of works (manuals, monographs, research articles, book chapters, etc.) there are still countless lexicographical products that have not been systematically described, analysed, and compared. This is due to factors such as the intricate web of personal, social, and intellectual events influencing lexicographical practice or the limitations in accessing documentary sources.The historical study of specialised lexicography is a clear example of this. The specialised bibliography on lexicographical production (dictionaries, glossaries, indexes, etc.) referring to fields such as Physics, Chemistry, Mining, or Mathematics is very abundant. However, this contrasts with the scant attention that other subjects such as Botany have received from historiography, despite the countless treatises, manuals, and lexicographical works that have been composed throughout history to record this specialised knowledge.Therefore, the aim of our work is to contribute to the historiography of Spanish botanical lexicography by examining the Nuevo diccionario de plantas medicinales estudiadas bajo el punto de vista botánico, médico y farmacéutico (1876), a work originally written in French by Auguste Héraud and translated into Spanish by Joaquín González-Hidalgo. Thus, the approach to our object of study has been formulated from a dual perspective that combines lexicographical description and historiographical interpretation. Specifically, the methodology employed is based on the description and analysis of both the lexicographical structures (frame structure, access structures, macrostructure, and microstructure) and their characteristics, and the social, cultural, and intellectual factors that conditioned their form and content.In this way, the conclusions will provide a more in-depth understanding of the history of botanical lexicography in Spanish and its lexicographical technique. Additionally, they will also be valuable for other disciplines related to lexicography and will contribute to the development of research related to the history of specialized lexicons or the reception of science in the Spanish language.
Keywords: lexicographical historiography; specialised dictionaries; botany; 19th century